“Estaciones de carga para vehículos eléctricos (Electrolineras) Caso de estudio Loja-Cuenca” - Méndez Jaramillo, Edgar Alcívar (2024)
This thesis research focuses on the exploration and analysis of suitable charging stations for electric vehicles, as well as their placement at strategic points along the Pan-American Highway E35 between the cities of Loja and Cuenca. It employs a methodology that integrates multiple selection criteria. Understanding governmental and international regulations is essential to determine the most appropriate type of charging station for electric vehicles, thus enabling the selection of the optimal type based on the route. It is noted through literature review that there is no Ecuadorian legislation establishing specific regulations on vehicle charging; instead, international standards shape the charging infrastructure in Ecuador. Consequently, it is concluded that a fast-charging station with an output power of 50 kW in mode 4, equipped with standard international connectors (CCS, CHAdeMO, and Type 2 AC), is the most suitable option for charging the majority of electric vehicles used in Ecuador. To determine the optimal location of charging stations, a study was conducted considering various relevant factors, such as the environment, economy, society, electricity, geography, and road quality. A methodology was employed that analyzes data provided by governmental and technological entities such as Google. The results obtained from this methodology indicate that only four out of the fourteen evaluated sites meet the necessary requirements to be considered suitable locations: Carigán, Saraguro, La Paz, and Yanuncay. During the electrical analysis, it was verified that the three-phase electrical network of Route E35, shared by two electric companies (EERSSA and CENTROSUR), meets quality standards by presenting harmonic factors below 8% and a power factor above 92%. It is relevant to note that EERSSA only has a three-phase network in Carigán (a sector north of the city of Loja) and Saraguro, which are the two cities with the highest population and energy demand, unlike CENTROSUR, where most localities have a three-phase network, except for the towns of Virgen de las Nieves and Susudel Keywords: Charging stations, electric vehicles, Pan-American route E35.